PERAN PROTEIN DAUN Mirabilis jalapa L SEBAGAI KEMOPREVENSI KANKER KULIT : PENELUSURAN MEKANISME ANTIINFLAMASI, RESTORASI SUPRESI IMUN DAN REGULASI APOPTOSIS - , Atina Hussaana, Dra.,M.Si.,Apt. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Protein isolated from Mirabilis jalapa L leaves (MJ protein) is a Ribosome-inactivating protein having apoptosis induction and antioxidant activity as superoxide dismutase (SOD). The induction of apoptosis plays an important role in the protection of UVB-induced skin damage, in which it eliminates DNA cell damage which thereby will be reducing the potential for gene mutation. Meanwhile, antioxidant activity contributes in the protection of UVB-induced skin damage since it will neutralize reactive oxygen species (ROS) thereby reducing lipid peroxides and immunosuppression. Since DNA damage and immunosuppression are factors in the UVB-induced skin carcinogenesis, we have therefore examined topical application of MJ protein to protect BALB/c mice from skin damage and carcinogenesis of skin cancer due to UVB irradiation. To study the photo-protective effect of MJ protein, the female BALB/c mice aged 6 week were exposed to the acute UVB radiation multiple dose 360 mJ/cm2 and it is observed against UVB-induced inflammation by considering its effect on reducing the middorsal skinfold thickness. Immunosuppression protection effect of MJ protein was evaluated against UVB and cis-urocanic acid (UCA)-induced immunosuppression by considering the influence of MJ protein in reducing suppression of contact hypersensitivity (CHS) response. The mice were exposed to the acute UVB radiation single dose 3 x 240 mJ/cm2, to find out the influence of MJ protein to the up-regulation of IL-10 and the depletion of IL-12 within epidermis which was observed immunohistochemically. Moreover, the influence of MJ protein to the regulation of apoptosis was observed by considering the number of apoptotic bodies formed as sunburn cells (SBC). The mice were exposed to chronic UVB radiation, a repeated dose of 360 mJ/cm2 irradiation for 65 times, with DMBA as co-carcinogen to study the chemo-preventive effect of MJ protein and to observe its potential in reducing the incidence of cancer and tumor multiplicity. The results indicates that MJ protein are able to (1) reduce UVB-induced inflammation since the middorsal skinfold thickness of mice treated with topical MJ protein decreased significantly (p<0.05) both in the control and treatment groups, from 1.62mm to 1.16